Childhood Asthma in Nigeria: A Review of the Burden and Challenges of Management - Kuti BP (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Bronchial asthma care professionals all over the world are faced with many challenges in managing children with asthma. This narrative review highlights the burden and specific challenges encountered by Nigerian health care professionals in the care of children with bronchial asthma and attempts to suggest ways of overcoming some of these challenges for optimal bronchial asthma care. Electronic search of relevant published articles from year 2000 to date was carried out using appropriate search engines for the following search words and phrases: "asthma in Nigerian children", "childhood asthma in Nigeria", "burden of asthma", "challenges," "prevalence" and "cost of bronchial asthma care." The findings revealed that childhood bronchial asthma was reported in all the geo-political zones of the country with evidence of increasing prevalence and male preponderance. Higher prevalence rates were reported in urban settings compared to rural settings and intermittent asthma was the most frequently reported form of the disease in Nigeria. Allergic rhinitis, with or without conjunctivitis were the most common co-morbidities, while respiratory tract infections, exposure to dust and physical exercise were the common triggers. Bronchial asthma was reported to affect school attendance, family finances and the quality of life of children and their caregivers. Reported challenges of childhood bronchial asthma in Nigeria included ignorance, poverty, stigma and poor adherence to medications by affected children and caregivers; inadequate work force and suboptimal knowledge of various cadres of health workers and poor health system as well as little or no availability of standard asthma care facilities at all levels of health care in Nigeria. Awareness creation, routine training and re-training of all cadres of health workers, provision of basic asthma care facilities and revamping of the health system may assist in overcoming the challenges.